STUDY OF PRESCRIPTION PATTERN OF ANTIEPILEPTICS DRUGS USED IN GSVM MEDICAL COLLEGE, KANPUR; A TERTIARY CARE HOSPITAL - Dr Sameer Siddiqui; Dr Pooja Agrawal; Dr Virendra Kushwah; Dr Alok Verma; Dr Amit Kumar; Dr Himanshu Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Epilepsy is a chronic neurological disorder characterized by recurrent, unprovoked seizures that can significantly impact an individual's quality of life. Current evidence suggests that the prescription of AEDs can vary significantly based on factors such as the type of epilepsy, patient demographics, and the presence of comorbid conditions.Aims & Objectives: The study aims to analyse prescription pattern of antiepileptic drugs used in Neuro medicine department of the tertiary care hospital, GSVM Medical College Kanpur, Uttar Pradesh.Material & Methods: An observational, cross-sectional study was carried out in Department of Pharmacology in collaboration with the Department of Neurology, G.S.V.M Medical College, Kanpur. Prescriptions of study participants were collected and further studied. All basic details and prescribed drugs were collected and entered in predesigned proforma.Results: It is observed that in 136 study subjects ‘prescriptions, the total number of prescribed antiepileptic drugs in study prescriptions was found to be 479 and the average number of prescribed antiepileptics per prescription encounter was found 3.52. It was observed that four fifth (79.41%) drugs were prescribed in polytherapy form i.e. more than two drugs and one fifth (20.59%) antiepileptics prescribed as monotherapy for management of diagnosed epilepsy diseases/disorders in study patients. Out of the total prescribed antiepileptic drugs, the most commonly prescribed antiepileptic drug was Carbamazepine (31.94%) followed by sodium valproate (23.59%) and Levetiracetam (21.29%). Conclusion: Overall, this study serves as a foundational assessment of AED prescribing practices at GSVM Medical College, Kanpur, and provides a basis for ongoing improvements in epilepsy management. By addressing the identified limitations and implementing the suggested recommendations, the institution can work towards optimizing patient care and aligning its practices with the latest advancements in epilepsy treatment